Assessing causal associations of hyperparathyroidism with blood counts and biochemical indicators: a Mendelian randomization study - Jiang, Yan; Chen, Rumeng; Xu, Shuling; Ding, Yining; Zhang, Mengling; Bao, Meihua; He, Binsheng; Li, Sen (Frontiers in Endocrinology, 2023)
Background The existing literature on the relationship of hyperparathyroidism with both blood counts and biochemical indicators primarily comprises observational studies, which have produced inconsistent findings. This study aimed to evaluate the causal relationship between hyperparathyroidism and blood counts and biochemical indicators. Methods Mendelian randomization (MR) analyses were conducted to investigate the associations between hyperparathyroidism and the identified 55 blood counts and biochemical indicators. The genome-wide association study (GWAS) for hyperparathyroidism data was obtained from FinnGen, while the GWASs for the blood counts and biochemical indicators were sourced from the UK Biobank (UKBB). Results The MR analysis using the inverse-variance weighted (IVW) method revealed potential causality between genetically predicted hyperparathyroidism and seven out of 55 blood counts and biochemical indicators. These markers include “Platelet count” (Beta = -0.041; 95% CI: -0.066, -0.016; p = 0.001), “Platelet distribution width (PDW)” (Beta = 0.031; 95% CI: 0.006, 0.056; p = 0.016), “Mean platelet volume (MPV)” (Beta = 0.043; 95% CI: 0.010, 0.076; p = 0.011), “Vitamin D” (Beta = -0.038; 95% CI: -0.063, -0.013; p = 0.003), “Calcium (Ca2+)” (Beta = 0.266; 95% CI: 0.022, 0.509; p = 0.033), “Phosphate” (Beta = -0.114; 95% CI: -0.214, -0.014; p = 0.025), and “Alkaline phosphatase (ALP)” (Beta = 0.030; 95% CI: 0.010, 0.049; p = 0.003). Conclusion The findings of our study revealed a suggestive causal relationship between hyperparathyroidism and blood cell count as well as biochemical markers. This presents a novel perspective for further investigating the etiology and pathological mechanisms underlying hyperparathyroidism.